Design, making, modeling and control of a mine prototype for research in mining ventilation - Salamanca, Juan Mauricio; Niño Merchán, John Jairo; Pérez, Adrián Felipe (Visión electrónica, 2014)
The main goal of a ventilation system is to supply mining activities with fresh and good-quality air. The major function of the ventilation control is to pump fresh air to the extraction shafts via tarpaulin tube to extract gases such as CH4, CO, SO2, H2S, NO2 and/or CO2. This operation depends on the type of extracted ore and also on the mining method applied. This paper describes the design, modeling and control of a mine prototype for studying mine ventilation. The prototype mine shown is designed to recreate a ventilation system that includes gas sensors that provide real-time measurements, also a control center where fan control can be carried out according to the percentages of detected gas, and precise knowledge about the actual energy consumption of fans.